Happiness : How to Build a Family out of Love and Spare Parts - Harpham, Heather (England : Oneworld Publications, 2018)
Happiness starts out as a charming courtship between hopelessly attracted opposites: Heather, a world-roaming California girl, and Brian, an intellectual, homebody writer, kind and slyly funny, but loath to leave his Upper West Side studio. Their magical interlude ends, full stop, when Heather becomes pregnant, Brian is sure he loves her, only he doesn't want kids. Heather returns to California to deliver their daughter alone, buoyed by family and friends. Mere hours after Gracie's arrival, Heather's bliss is interrupted when a nurse wakes her, "Get dressed, your baby is in trouble." This is not how Heather had imagined new motherhood, alone, heartsick, an unexpectedly solo caretaker of a baby who smelled "like sliced apples and salted pretzels" but might be perilously ill. Brian reappears as Gracie's condition grows dire; together Heather and Brian have to decide what they are willing to risk to ensure their girl sees adulthood. The grace and humor that ripple through Harpham's writing transform the dross of heartbreak and parental fears into a clear-eyed, warm-hearted view of the world. Profoundly moving and subtly written, Happiness radiates in many directions, new, romantic love; gratitude for a beautiful, inscrutable world; deep, abiding friendship; the passion a parent has for a child; and the many unlikely ways to build a family. Ultimately it's a story about love and happiness, in their many crooked configurations.
Keywords: Blood -- Diseases; Parent and child -- Biography; Health and Wellbeing